Seagrass Cholorophyll-a, Biomass and Carbon Algorithms Based on the Field and Sentinel-2A Satellite Data at Karimunjawa Island, Indonesia - Agus Hartoko; Yoan Teresia Sembiring; Nurul Latifah (Science and Technology Indonesia, 2021)
Chlorophyll-a in seagrass biomass is functioned for the photosynthetic process and store the organic carbon in their biomass of the leaf, rhizome, and root. Ecologically has functioned as blue carbon in reducing global warming adaptation and mitigation strategy. The study aimed to explore seagrass species, chlorophyll-a content, biomass and carbon stock at Karimunjawa Island. Develop algorithms of the Sentinel-2A satellite data based on field seagrass chlorophyll-a, biomass and carbon and at Pokemon and Bobby beach Karimunjawa Island. Four species of seagrass found at Bobby and Pokemon beach are Holodule pinifolia with a density of 160.44 ind.m−2 , Enhalus acoroides with 26.22 ind.m−2, Halophila ovalis with 6.67 ind.m−2 and Thalassia hemprichii with 4.44 ind.m−2.The lowest seagrass chlorophyll-a is 5.854 mg.ml−1 found in H. pinifolia and the highest is 20.819 mg.ml−1found in E. acoroides at Pokemon beach. The range of seagrass chlorophyll-a at Bobby beach was 3.485 - 14.133 mg.ml−1 in T. hemprichii. The smallest individual biomass dry weight was found in T.hempirichii with 1.32 g.dry.weight per individu, and the biggest in E.acoroides with 6.98 g.dry.weight per individu. The highest seagrass biomass at Pokemon beach was in E. acoroides with 236.93 g.m−2 which has a wide leaf morphology and the lowest in H. pinifolia with 75.91 g.m−2 with the smallest leaf morphology. The range of seagrass biomass at Bobby beach is 97.62 - 264.48 g.m−2 which is dominated by T.hempirichii. The range of seagrass carbon was 109.63 - 136.82 gC.m−2at Pokemon beach, and in the range of 95.00 - 114.01 gC.m−2 at Bobby beach. Algorithm of seagrass chlorophyll-a = -36.308 (B3/B4)2 – 140.41(B3/B4) + 83.912 ; biomass = -7028.3 (B3/B4)2 + 14948 (B3/B4) – 7764.4; carbon = -17.529(B2/B3)2 + 143.82(B2/B3) – 5.3362 for Pokemon beach. Algorithm of chlorophyll-a = 455.02 (B2/B4)2 + 823.72 (B2/B4) + 375.48; biomass = -14699 (B3/B2)2 + 28395(B3/B2) – 13537; and carbon = - 0.001(B3/B4)2+ 0.209(B3/B4) - 10.203 for Bobby beach. The use of Band-2 (0.490 ????m), Band-3 (0.560 ????m) and Band-4 (0.665 ????m) Sentinel-2A satellite data in the development of seagras chlorophyll-a, biomass and carbon algorithm was found to be significant.